Implementation of Mudharabah Agreement Between Boat Owners and Fishermen in Teluk Meuku Village, Babalan District, Langkat Regency, Reviewed From the View of the Syafi'i School - Alfina Yanti; Muhammad Nur Iqbal (Fox Justi : Jurnal Ilmu Hukum, 2025)
The aim of this research is to understand how the mudharabah contract is applied between boat owners and fishermen in Meuku Bay Village, Babalan Subdistrict, Langkat Regency, and to examine the perspective of the Shafi'i school regarding its implementation. This study uses a descriptive qualitative approach. Data were obtained from both primary and secondary sources. Data collection techniques included observation, interviews, and documentation. The analysis was conducted through data reduction, data presentation, and conclusion drawing. The agreement between boat owners and fishermen in Meuku Bay Village uses a mudharabah contract that is made orally, without anything written agreement — based solely on mutual trust. This contract emphasizes key points such as the cooperation system, profit- sharing system, and others important elements. The practice of mudharabah in this village align with the Shafi'i school in several aspects : there are two parties involved (the boat owner and the fisherman), capital and profits are shared based on mutual agreement, and the boat owner give bonuses to the fishermen. However, there are also those aspects that contradict the Shafi'i perspective — specifically, when losses occur, the fishermen (as fund managers) bear the burden of compensation, even though according to the Shafi'i school, if the loss is not due to negligence, it should be borne solely by the capital provider without imposing liability on the manager.